Effect of Corn Stalk Biochar on the Evolution of Water Evaporation and Cracking of Soil. (23rd June 2022) - Zhang, Dingyang; Lv, Qihang; Xu, Xinyang; Li, Bin; Sun, Min
Abstract : The evolution of water evaporation and cracking of soil affected by corn stalk biochar is experimentally investigated. Water evaporates from the soil surface, causing shrinkage in soil body and forming cracks, which significantly lead to crop nutrient loss, groundwater pollution, and land salinization. Biochar is a recyclable natural material widely used in improving the water retention and suppression of cracking of soils. Free desiccation tests were conducted with adding the biochar contents of 0%, 4%, and 8%. The variation of water evaporation amount and the development of cracking were recorded and disposed. The results show that the evaporation process can be changed due to the addition of biochar contents. The evaporation rate can be divided into three phases of a constant rapid evaporation phase, a fluctuated evaporation phase, and a residual evaporation phase. A sudden increase at around 30% of moisture content in evaporation rate indicated that the crack began to develop and extend greatly, which increased the evaporation surface area. The residual moisture contents of soils with biochar contents of 4% and 8% increased by 105.56% and 88.38% than those of soil without biochar, respectively. The crack ratio reduced by 32.39% and 15.31% with the addition of biochar contents of 4% and 8%, respectively. A three-level crack was observed during evaporation process, where a second and third crack developed less with the addition of biochars. The corn stalk biochar improves the integrity of soil bodies and increases the connection of soil particles for more water storing between the biochar particles and soil particles. It can be concluded that corn stalk biochars are able to delay the evaporation and cracking developing in cohesive soils, which may be beneficial for crops in dry area.